Associating The Gap: The Role Of Medical Nurses With Lab Technician Skills In Healthcare. A New Appraisal (Journal of Namibian Studies : History Politics Culture, 2023)
The integration of medical nursing and laboratory technology has transformed the landscape of modern healthcare, giving rise to a new breed of professionals with multifaceted skills and competencies. This article examines the role of medical nurses with lab technician skills in bridging the gap between clinical care and laboratory diagnostics. By seamlessly integrating clinical expertise with technical proficiency, these versatile professionals enhance diagnostic accuracy, streamline healthcare delivery, and improve patient outcomes. Through a comprehensive exploration of their key skills, competencies, and the benefits they bring to healthcare delivery, this article sheds light on the transformative potential of this hybrid role. As healthcare continues to evolve, the demand for individuals proficient in both medical nursing and laboratory technology will only grow, underscoring the importance of investing in education and training programs that equip nurses with the diverse skill set needed to meet the complex needs of patients in the 21st century.